Optical coherence tomography and coherence techniques : 22-24 June 2003, Munich, Germany - Optical Coherence Tomography and Coherence Techniques Conference (2003 : Munich, Germany); Drexler, Wolfgang (Bellingham, WA : SPIE, 2003)
40